Comparison of dairy wastewater and synthetic medium for biofuels production by microalgae cultivation. Issue 7 (3rd April 2018) - Shu, Qing; Qin, Lei; Yuan, Zhenhong; Zhu, Shunni; Xu, Jin; Xu, Zhongbin; Feng, Pingzhong; Wang, Zhongming
ABSTRACT: This study is concerned with comparing raw dairy wastewater (DWW) with blue-green medium (BG11 medium) for biofuel production. Three microalgae strains ( Chlorella sp., Scenedesmus sp., and Chlorella zofingiensis ) were cultured in tubular bubble column photobioreactors with two media separately. After 8 days of cultivation, DWW was demonstrated to be more suitable medium for microalgae biomass and lipid production than BG11 medium. The biomass and lipid produced within wastewater provided suitable feedstocks for anaerobic digestion and biodiesel conversion. Nutrients in wastewater were efficiently removed (>90% total nitrogen removal, approximately 100% ammonia removal, and >85% total phosphorus removal) during this process.